(untitled) (Research, Society and Development, 2021)
COVID-19 is a disease caused by a new viral pathogen called Sars-Cov-2. This disease presents symptoms that vary on a global scale of: mild, moderate, severe, very severe and death depending on the response of the patient’s organism. Currently, this pathogen is responsible for causing one of the largest human-experienced plagues worldwide. In addition to the health problems caused by the disease, humanity is also dealing with health problems considered secondary, such as mental illness, especially of Brazilian higher education students. Considering this information, the present work aims to present a document from a review of the literature on the impacts caused by the Sars-cov-2 pandemic on the mental health of the population of Brazilian academics. The methodological procedure of the work consists of a review of the literature, of qualitative, descriptive and exploratory character, carried out in journals of scientific articles, in repositories of universities and in government websites. During the research, it was observed that the greatest mental disorders developed by these people in the pandemic period were: depression, stress, fear, anxiety, insomnia, aggressiveness, irritability and anguish. Thus, it is concluded that one of the strategies that could minimize the effects of the pandemic in this population would be the availability of free online psychological treatment provided by the government and/or higher education institutions in the form of extension projects developed by academics of health courses.